Current and future targeted therapies for severe asthma: Managing treatment with biologics based on phenotypes and biomarkers. (August 2019) - Santus, Pierachille; Saad, Marina; Damiani, Giovanni; Patella, Vincenzo; Radovanovic, Dejan
Graphical abstract: Abstract: Asthma is a respiratory disorder with considerable heterogeneity in aetiology, triggers, clinical characteristics and response to therapy. This diversity reflects different inflammatory pathways that can be subdivided into clinically similar categories called phenotypes, or pathogenically comparable groups called endotypes. In recent years, a great amount of research has been dedicated to the investigation and understanding of the heterogeneity of asthma pathophysiology and to the identification of treatable traits, biomarkers, mediators and therapeutic targets. Severe asthma is defined as an uncontrolled disease despite a maximal conventional therapeutic approach. While, to date, some target therapies showing improvements in lung function, asthma symptoms and a reduction of the annual rate of exacerbations in patients with severe asthma have been already approved, other treatments are currently being studied, specifically targeting Type 2 asthma. Further progress however, is still needed to tackle the molecular pathways for non-Type 2 asthma. The aim of the present narrative review is to discuss and examine the indication, mechanisms of action and therapeutic effects of currently available and emerging biologic agents for the treatment of severe asthma.